Timeliness of Financial Reporting: An Empirical Study in Indonesia Stock Exchange - IKA MERDEKAWATI; REGINA J. ARSJAH (The Indonesian Journal of Accounting Research, 2013)
This study empirically analyzed timeliness of financial reporting in Indonesia. Timelines of financial reporting are measured by audit lag and reporting lag. This study utilized an unbalanced panel of 700 firm-years of companieslisted on the Indonesia Stock Exchange during the period 2007-2009. The mean of audit lag is 74 days and the mean of reporting lag is 94 days. It is found that corporate governance and audit opinion negatively affect both audit lag and reporting lag, whereas firm size positively affectsaudit lag and reporting lag. Debt ratio only negatively affects reporting lag. Auditor’s firm, profitability, price earnings ratio and dividend payout ratio do not significantly affect either audit lag or reporting lag. Inter-industry analysis of audit lag and reporting lag reported that the financial industry has the shortest audit lag and reporting lag. The trade, service and investment industries have the longest audit lag whereas the property, real estate and building construction industries have the longest reporting lag.